PENGARUH LATIHAN DUMBBELL LUNGE TERHADAP EXPLOSIVE POWER OTOT TUNGKAI PADA ATLET ATLETIK LARI 100 M PPLM DISPORA RIAU - M. Hariadi Hidayat Hidayat; Ramadi '; Ni Putu Nita Wijayanti Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract This study was conducted to determine whether there are effects of exercise on the dumbbell lunge explosive power leg muscle  in atheletic sprinter so that when doing a start run to get maximum results.This research is a form of research with experimental treatment (Experimental), with a population of athletes sprinter 100 meter in Pplm Dispora Riau, in this study all population data of 6 people. The instruments used in this research is standing broadjump, which aims to measure legexplosive power in the horizintal direction. Afterthat, data is processed with statistics, to the test normality of the test at significant level 0,05α lilifors. Hypothesis proposed, exercise effect of Lateral Cone Hops To Explosive Muscle Power Limbs.Based on t test analysis produces 0,2139 Thitung and 0,2015 Ttabel, its means Thitung>Ttabel. Based on analysis of statistical data, there are on Pree-test average was 0,226 and post-test average was 0,319 data is normal. Then, there is a Exercise Effect of dumbbell lunge explosive power leg muscle in atheletic sprinter 100 meter so that of man athlete Pplm Dispora Riau. Keywords: dumbbell lunge